Identifikasi Sumber Energi Terbarukan (SET) - Trian Zulhadi; Said Fazli (Kutubkhanah, 2012)
This study aims to identify renewable energy resources in Riau province. This study is very important because Riau has abundant natural resources, such as solar, wind, water, biogas, biomass and many more. The research findings in four regencies, namely Indragiri Hilir, Rokan Hilir, Kuantan Singingi and Rokan Hulu, show that water, wind, solar, and biomass energy are potential to be developed into Micro Hydro Power Plant, Water Power Plant, Solar Power Plant and Biomass Power Plant.